Class act - Craft, Jerry (New York, NY Quill Tree Books, an imprint of HarperCollinsPublishers/Harper Alley, 2020)
"Eighth grader Drew Ellis recognizes that he isn't afforded the same opportunities, no matter how hard he works, that his privileged classmates at the Riverdale Academy Day School take for granted, and to make matters worse, Drew begins to feel as if his good friend Liam might be one of those privileged kids and is finding it hard not to withdraw, even as their mutual friend Jordan tries to keep their group of friends together."--Provided by publisher.
"Companion to the Newbery Medal Winner 'New Kid'"--Front cover.
Accelerated Reader
Keywords: African American school children -- Comic books, strips, etc; African American school children -- Juvenile fiction; Middle schools -- Comic books, strips, etc; Middle schools -- Juvenile fiction; Private schools -- Comic books, strips, etc; Private schools -- Juvenile fiction; Race relations -- Comic books, strips, etc; Race relations -- Juvenile fiction; Stereotypes (Social psychology) -- Comic books, strips, etc; Stereotypes (Social psychology) -- Juvenile fiction; Cartoonists -- Comic books, strips, etc; Cartoonists -- Juvenile fiction; African Americans -- Fiction; Private schools -- Fiction; Individuality -- Fiction; JUVENILE FICTION / Comics & Graphic Novels / Humorous; JUVENILE FICTION / Diversity & Multicultural; JUVENILE FICTION / Boys & Men; African Americans; Cartoonists; Middle schools; Race relations; Stereotypes (Social psychology); African Americans -- Comic books, strips, etc; Private schools -- Comic books, strips, etc; Individuality -- Comic books, strips, etc; African Americans -- Fiction; Private schools -- Fiction; Individuality -- Fiction; Graphic novels; Comic books, strips, etc; Coming-of-age comics; Graphic novels; Social problem fiction; Graphic novels; Graphic novels; Coming-of-age comics; Social problem fiction; School comics